Reconstruction of sciatic nerve after traumatic injury in humans - factors influencing outcome as related to neurobiological knowledge from animal research - Maripuu, Amanda; Björkman, Anders; Björkman-Burtscher, Isabella M; Mannfolk, Peter; Andersson, Gert; Dahlin, Lars B (Journal of Brachial Plexus and Peripheral Nerve Injury, 2012)
Background The aim was to evaluate what can be learned from rat models when treating patients suffering from a sciatic nerve injury.Methods Two patients with traumatic sciatic nerve injury are presented with examination of motor and sensory function with a five-year follow-up. Reconstruction of the nerve injury was performed on the second and third day, respectively, after injury using sural nerve grafts taken from the injured leg. The patients were examined during follow-up by electromyography (EMG), MRI and functionalMRI (fMRI) to evaluate nerve reinnervation, cell death in dorsal root ganglia (DRG) and cortical activation; factors that were related to clinical history in the patients.Results One patient regained good motor function of the lower leg and foot, confirmed by EMG showing good activation in the leg muscles and some reinnervation in the foot muscles, as well as some sensory function of the sole of the foot. The other patient regained no motor (confirmed by EMG) or sensory function in the leg or foot. Factors most influential on outcome in two cases were type of injury, nerve gap length and particularly type of reconstruction. A difference in follow-up and rehabilitation likely also influence outcome. MRI did not show any differences in DRG size of injured side compared to the uninjured side. fMRI showed normal activation in the primary somatosensory cortex as a response to cutaneous stimulation of the normal foot. However, none of the two patients showed any activation in the primary somatosensory cortex following cutaneous stimulation of the injured foot.Conclusions In decision making of nerve repair and reconstruction data from animal experiments can be translated to clinical practice and to predict outcome in patients, although such data should be interpreted with caution and linked to clinical experience. Rat models may be useful to identify and study factors that influence outcome after peripheral nerve repair and reconstruction; procedures that should be done correctly and with a competent team. However, some factors, such as cognitive capacity and coping, known to influence outcome following nerve repair, are difficult to study in animal models. Future research has to find and develop new paths and techniques to study changes in the central nervous system after nerve injury and develop strategies to utilize brain plasticity during the rehabilitation.
Keywords: Sciatic nerve injury; Nerve regeneration; Reconstruction; Outcome; fMRI; Dorsal root ganglia